Unaccompanied Minors and Separated Refugee Children in Sweden: An Outlook on Demography, Education and Employment - Aycan Celikaksoy; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2015)
The number of unaccompanied minors has increased over the past ten years in Sweden, the European country that receives the most children from this group. Some of them emigrate after a period of time in Sweden, but the vast majority stay. Most of the arriving children are teenage boys who have not yet turned 18. However, the largest increase over the latest years is observed for the younger age groups. Furthermore, gender composition is also age dependent, where it is quite balanced for the younger age groups unlike the oldest age group. In the years following their arrival, most of them are enrolled in schools. When it comes to those aged 20 or over, the proportion undergoing education is higher among women but a higher proportion of men are employed. The group that neither works nor studies is much larger among women than among men.
Keywords: J13; J15; 330; unaccompanied minors; refugee children; migration; education